2023
DOI: 10.3390/agronomy13010209
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Length of Storage and Chemical Additives on the Nutritive Value and Starch Degradability of Reconstituted Corn Grain Silage

Abstract: The aim of this study was to evaluate the feed quality of reconstituted corn grain silage (RCGS), treated with chemical additives and stored for 15, 30, or 60 d in 5-L plastic buckets. Dry ground corn was rehydrated to 350 g·kg−1 and treated with either polysorbate 80 (2 L·t−1) (POL), propionic acid 28% (2 L·t−1) (PRO), Mycoflake™ (2 L·t−1-blend polysorbate 80 and propionic acid) (MYC) or nothing (CON). The effect of the length of storage was combined in a factorial arrangement with the additives. Ammonia-N in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
0
1
Order By: Relevance
“…These results corroborate with the findings of Hoffman et al [91], who observed continuous degradation activity of the protein matrix up to 240 days of storage. However, it is interesting to note the discrepancy with the results of Oliveira et al [52], who reported a different pattern for NH 3 -N in silages treated with Mycoflake™, showing a slight increase in CP levels after 30 days of ensiling, indicating possibly an increase in matrix proteolysis; the concentration of NH 3 -N was considerably higher, reaching similar levels. These observations highlight the complexity and variability in the effects of additives on the composition and degradation of the protein matrix in silages.…”
Section: Discussioncontrasting
confidence: 73%
“…These results corroborate with the findings of Hoffman et al [91], who observed continuous degradation activity of the protein matrix up to 240 days of storage. However, it is interesting to note the discrepancy with the results of Oliveira et al [52], who reported a different pattern for NH 3 -N in silages treated with Mycoflake™, showing a slight increase in CP levels after 30 days of ensiling, indicating possibly an increase in matrix proteolysis; the concentration of NH 3 -N was considerably higher, reaching similar levels. These observations highlight the complexity and variability in the effects of additives on the composition and degradation of the protein matrix in silages.…”
Section: Discussioncontrasting
confidence: 73%